THE IMPORTANCE OF THE PROGRAM OF ACQUISITION OF FOODS FOR FAMILIES AND BENEFICIARY ENTITIES IN THE NOVA ALTA PAULISTA REGION - Veloso, Fernando [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2017)
The text aims to analyze the distribution of the products of The Programa de Aquisicao de Alimentos [Food Acquisition Program] (PAA) in the Simultaneous Donation modality that buys from family farmers and, subsequently, donates the products to families and social organizations in the cities of Adamantina, Tupi Paulista e Pauliceia located in the west of Sao Paulo State. In the methodology, a literature review was conducted, collecting secondary data and conducting field research through interviews with representatives of organizations and beneficiary families. In relation to beneficiary families, the results are more satisfactory in Pauliceia and Tupi Paulista, considering that the people interviewed were placed mostly in CadUnico and beneficiaries of other social programs. In turn, representatives of organizations emphasized the decrease in the cost of food and the menu of enrichment due to the quality and diversity of products of family farmers. However, the budget cuts of the PAA, which have taken place since the year 2015, by the Federal Government, have resulted in already noticeable consequences in the municipalities of the Nova Alta Paulista region affecting, negatively, family farmers, beneficiary entities and families, in an uncertain scenario of continuity of the program.
Keywords: Public policies; Food Acquisition Program; Food and nutrition security